2004
DOI: 10.1103/physrevb.70.174401
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous scaling behavior of the dynamical spin susceptibility ofCe0.925La0.075Ru2<

Abstract: Inelastic neutron scattering measurements have been performed on single crystals of the heavy fermion compound Ce0.925La0.075Ru2Si2 in broad energy [0.1, 9.5 meV] and temperature [40 mK, 294 K] ranges in order to address the question of scaling behavior of the dynamical spin susceptibility at the quantum critical point of an itinerant magnetic system. For two wavevectors Q corresponding to uncorrelated and antiferromagnetically correlated spin fluctuations, it is found that the dynamical spin susceptibility χ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 43 publications
9
87
0
Order By: Relevance
“…Thus, if we are to distinguish quantum critical scaling from geometry-induced mimicking of scaling, then we must scrutinize the scaling function itself. In the present work we have found a scaling relation that can be cast into a similar form as the scaling functions found in the literature [12][13][14][15][16]40 IЈ͑q,E,T͒ ϳ Љ͑q,E,T͒…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, if we are to distinguish quantum critical scaling from geometry-induced mimicking of scaling, then we must scrutinize the scaling function itself. In the present work we have found a scaling relation that can be cast into a similar form as the scaling functions found in the literature [12][13][14][15][16]40 IЈ͑q,E,T͒ ϳ Љ͑q,E,T͒…”
Section: Discussionsupporting
confidence: 63%
“…Aronson et al 13,14 found that UCu 5−x Pd x scales with a =1/ 3 and b = 1 in their original observation of scaling in QCP systems. Further, Schröder et al, 12 Knafo et al, 40 and Montfrooij et al 15 16 reported an exponent of a = 0.2-0.5 ͑and b =1͒ for URu 2−x Re x Si 2 for x = 0.2-0.6, respectively. Note that it is not clear at present, given the range of values reported for the exponent a, whether there is an underlying connection between the exponent a of the scaling relation and the ratio d / z of the effective dimension d and the dynamical exponent z.…”
Section: Discussionmentioning
confidence: 97%
“…The measured scattering function can be 02003-p. 19 Collection SFN easily related to a microscopic description of the studied system using either matrix elements, spin-spin correlation functions or the dynamical spin susceptibility formalism. Finally polarized Inelastic Neutron Scattering allows not only to unambiguously show the magnetic nature of the measured spectrum but also to gain more insight into detailed characteristics of the magnetic excitation.…”
Section: Resultsmentioning
confidence: 99%
“…(1.5). Figure 8 shows the scattering function measured in CeRu 2 Si 2 at the wave-vector Q = (0.69, 1, 0) [19]. In this compound, the spin dynamics is basically governed by the Kondo relaxation.…”
Section: -P11mentioning
confidence: 99%
“…The panel A of Fig. 15 reports (T 2/3 χ ′′ ) N extracted from measurements of the inelastic neutron scattering spectrum on the HF metal Ce 0.925 La 0.075 Ru 2 Si 2 [52]. The data (T 2/3 χ ′′ ) N exhibit the scaling behavior over three orders of the variation of both the function and the variable.…”
Section: Quantum Spin Liquidmentioning
confidence: 99%